The reluctant entrepreneur : turning dreams into profits - Masterson, Michael, 1950- (Hoboken, N.J. : John Wiley & Sons, 2012)
'Intelligent strategies for starting and growing a small business with minimal personal financial riskA comprehensive guide for entrepreneurs from one of the most successful business creators in recent years, The Reluctant Entrepreneur: Turning Dreams into Profits addresses the fears and misconceptions that many people have about starting their own businesses, walking prospective owners through the necessary decisions they need to make before even putting a business plan in place.Presenting solid, reliable strategies based on author Michael Masterson's own successful practices, and debunking some common illusions entrepreneurs have about their businesses, the book is a vital resource for anyone looking to avoid the pitfalls that threaten fledgling companies. Packed with insights from an entrepreneur who has launched and sold dozens of business, presented in a lively and conversational style Some 600,000 new businesses are launched each year and with an uncertain economy, more and more people are looking for a stream of income separate from their 9 to 5 job Filled with highly applicable advice that budding and professional entrepreneurs can start using immediately Essential reading for small business owners and both first time and established entrepreneurs, The Reluctant Entrepreneur presents the smart strategies on starting and growing a small business that can make launching your own company a cinch'--Provided by publisher.
Includes index.
Keywords: Entrepreneurship; New business enterprises -- Management; Small business -- Management; BUSINESS & ECONOMICS / Entrepreneurship